Effects of DNA Topology on Transcription from rRNA Promoters in Bacillus subtilis - Sudzinová, Petra; Kambová, Milada; Ramaniuk, Olga; Benda, Martin; Šanderová, Hana; Krásný, Libor (Microorganisms, 2021)
The expression of rRNA is one of the most energetically demanding cellular processes and, as such, it must be stringently controlled. Here, we report that DNA topology, i.e., the level of DNA supercoiling, plays a role in the regulation of Bacillus subtilis σA-dependent rRNA promoters in a growth phase-dependent manner. The more negative DNA supercoiling in exponential phase stimulates transcription from rRNA promoters, and DNA relaxation in stationary phase contributes to cessation of their activity. Novobiocin treatment of B. subtilis cells relaxes DNA and decreases rRNA promoter activity despite an increase in the GTP level, a known positive regulator of B. subtilis rRNA promoters. Comparative analyses of steps during transcription initiation then reveal differences between rRNA promoters and a control promoter, Pveg, whose activity is less affected by changes in supercoiling. Additional data then show that DNA relaxation decreases transcription also from promoters dependent on alternative sigma factors σB, σD, σE, σF, and σH with the exception of σN where the trend is the opposite. To summarize, this study identifies DNA topology as a factor important (i) for the expression of rRNA in B. subtilis in response to nutrient availability in the environment, and (ii) for transcription activities of B. subtilis RNAP holoenzymes containing alternative sigma factors.
Keywords: transcription; Bacillus subtilis; ribosomal RNA; DNA topology